Antisemitism on the rise : the 1930s and today - Kohen, Ari, 1977-; Steinacher, Gerald (Contemporary Holocaust studies., 2021)
"A collection of historical and contemporary research and essays, Antisemitism on the Rise: the 1930s and Today evaluates the progression of antisemitism from the interwar period to today and provides examples for how to effectively teach current research and antisemitism as a whole";